Variabilidad climática en zonas de alto riesgo del cantón Quevedo, Ecuador - Flores Bazurto, Evelyn Elizabeth (2022)
One of the effects of climate change is the increased frequency and intensity of related adverse events. The experience accumulated worldwide shows that the negative impacts of these phenomena can be considerably reduced by analyzing local climate trends. The present investigation whose objective is to evaluate urban resilience against climate change and variability in the Quevedo canton, diagnose adverse events generated by climatic conditions and determine the climatic variability of the canton based on the parameters of precipitation and temperature, contributes to the generation of knowledge on the effects of climate change in the study area and the path towards a resilient community. The data analyzed comes from international databases and information from INAMHI. The univariate method of the Criterion of Differences was used to fill in the missing values. In the temporal analysis of climatic variability, the methodology of ombrothermal diagrams was applied, verifying the increase of more than 1° in the average annual temperature in the last decade. The modeling also revealed the increase in the destructive potential of the rains, predicting an increase in their intensity (191.6 mm of precipitation in 1 hour). The integration of the results of the climate analysis with the data of the emergencies of natural origin attended by the Integrated Security Service ECU 911 in the study area in the period 2013 - 2018 and the analysis of the results of the interviews and surveys to the main actors social conditions served as the basis for the formulation of prevention strategies to face the effects of climate change. The implementation of these strategies would allow the creation of a system of preventive measures and the strengthening of the training and culture of resilience in the population.